Co-designing strategies to support patient partners during a scoping review and reflections on the process: a commentary - McCarron, Tamara L. (Res Involv Engagem, 2021)
BACKGROUND: Patient partners can be described as individuals who assume roles as active members on research teams, indicative of individuals with greater involvement, increased sharing of power, and increased responsibility than traditionally described by patient participants who are primarily studied. A gap still remains in the understanding of how to engage patients. The objective of this commentary is to describe the involvement of four patient partners who worked with researchers during a scoping review. MAIN BODY: We describe approaches to meaningfully engage patient partners in conducting a scoping review. Patient partners were recruited through existing patient networks. Capacity development in the form of the training was provided to these four patient partners. Engagement strategies were co-designed with them to address potential barriers of involvement and acquiring the necessary skills for the successful completion of this scoping review. CONCLUSION: Involving patients partners early in the project established the foundational relationship so patient partners could contribute to their fullest. We witnessed the success of working alongside patient partners as members of the research team with a clear and mutually agreed upon purpose of the engagement in health research activities and how this seemed to contribute to an effective and rewarding experience for both researcher and patient partner. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40900-021-00272-3.